2020
DOI: 10.3389/fendo.2020.544658
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphisms rs7093069-IL-2RA, rs7138803-FAIM2, and rs1748033-PADI4 in the Group of Adolescents With Autoimmune Thyroid Diseases

Abstract: Introduction: The pathogenesis of autoimmune thyroid diseases is complicated and not completely known. Among the causes of thyroid autoimmunity, we distinguish genetic predisposition and environmental factors. Graves' disease and Hashimoto's thyroiditis are associated with a disturbance of immune tolerance of thyroid antigen molecules. The IL2RA gene is located on chromosome 10 and encodes the interleukin 2 receptor (IL2RA), which is expressed by the regulatory T-cells (Tregs) responsible for suppression. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…This result was of particular interest, because it showed that GD and GO shared a common genetic susceptibility locus, which needs to be further investigated in view of the fact that both diseases are different in pathogenesis. Previous studies found that IL2RA/rs7093069 was significantly associated with susceptibility to GD in Caucasian [40,41], while the results of our study showed that IL2RA/rs7093069 was not significantly associated with GD susceptibility in Southwest China. The reason for the inconsistent results may be due to different genetic background of people in different regions and the sample size involved in the study.…”
Section: Discussioncontrasting
confidence: 94%
“…This result was of particular interest, because it showed that GD and GO shared a common genetic susceptibility locus, which needs to be further investigated in view of the fact that both diseases are different in pathogenesis. Previous studies found that IL2RA/rs7093069 was significantly associated with susceptibility to GD in Caucasian [40,41], while the results of our study showed that IL2RA/rs7093069 was not significantly associated with GD susceptibility in Southwest China. The reason for the inconsistent results may be due to different genetic background of people in different regions and the sample size involved in the study.…”
Section: Discussioncontrasting
confidence: 94%
“…Genetic predisposition and environmental factors contribute to the development of autoimmune thyroid disease. Polymorphism of genes occurs in genetically predisposed individuals [ 13 ]. Deficiency in suppressor T cells and loss of self-tolerance are mainly involved in the pathogenesis of GD [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4, IL-2RA and PTPN22) and thyroid-specific genes (e.g. TG and TSHR) (13,14,15). HCP5 polymorphisms have been associated with a younger age at GD onset (16,17).…”
Section: Definitive Treatment In Pediatric Gd -Radioiodine (Rai)mentioning
confidence: 99%